Supply chain resilience: Measure, risk assessment and strategies - Cuihong Yang; Kailan Tian; Xiang Gao (Fundamental Research)
Supply chains in modern economy are fragmented and globalized following international specialization. It brings economic benefits while at the same time may raise propagated risks along supply chains. Facing the same disastrous event, some firms/regions/countries appeared to cope with it more quickly and efficiently due to their resilient supply chains. In the current world where major emergencies and disasters occur frequently, we urgently call for more effective strategies to strengthen supply chain resilience (SCR). We further stress that SCR strategies build on more solid scientific research including properly measuring SCR at both micro- and macro- levels and conducting appropriate assessment of economic risks to supply chain disruptions.